2009
DOI: 10.3168/jds.2009-2115
|View full text |Cite
|
Sign up to set email alerts
|

Using gait score, walking speed, and lying behavior to detect hoof lesions in dairy cows

Abstract: The objective was to determine whether changes in the different components of gait, walking speed, and lying behavior were associated with hoof pathologies in lactating Holstein cows. In experiment 1, 53 cows had their gait scored, their walking speed estimated, and their lying behavior monitored before clinical assessment of the hooves. Multiparous cows with ulcers scored higher than cows without ulcers for overall gait score [numerical rating score (NRS); 3.3 +/- 0.2 vs. 2.8 +/- 0.2], back arch, joint flexio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
186
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(218 citation statements)
references
References 28 publications
24
186
6
2
Order By: Relevance
“…For example animals will have longer lying bouts (Chapinal et al, 2009) or will lie down quickly after feeding (Grégoire et al, 2013). In the present study, the latency to lie down in the hour following feeding did not seem to accurately reflect lameness.…”
Section: Discussioncontrasting
confidence: 79%
“…For example animals will have longer lying bouts (Chapinal et al, 2009) or will lie down quickly after feeding (Grégoire et al, 2013). In the present study, the latency to lie down in the hour following feeding did not seem to accurately reflect lameness.…”
Section: Discussioncontrasting
confidence: 79%
“…In spite of that, Chapinal et al (2009) found no differences in lying time for animals with digital dermatitis or sole ulcers when compared with animals without lesions. Controversy about lying time spent by lame cows might be due to the differences about how cows were housed and the periodicity of behavioral observations (Pavlenko et al, 2011).…”
Section: Discussionmentioning
confidence: 61%
“…For further analysis, cows were grouped into two groups, non-lame or low LS (LS≤3) and lame cows or high LS (LS>3), irrespectively of the day of measurement (Chapinal et al, 2009). In the evaluation of the factors that influenced the behavioral variables, the statistical model included the effects of locomotion score (n = 2; low (LS≤3) and high (LS>3)), day (n = 2; days -1 and 6, respectively, pre and post-trimming plus treatment), and lesion (n = 2; infectious diseases and non-infectious diseases).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations